Alternative splicing of the Rbm24 gene is essential for cochlear hair cell stereocilia integrity and hearing function in mice - Chunjiao Sun; Jingshuang Zhao; Nana Li; Xuebo Yao; Yanfei Wang; Chul Hoon Kim; Jinwoong Bok; Anthony W. Peng; Zhigang Xu (Proceedings of the National Academy of Sciences, 2026)
Cochlear hair cells are the mechanosensitive receptor cells responsible for detecting sound information. They are characterized by their apical F-actin-filled stereocilia that are essential for mechano-electrical transduction. Previously, we and other groups reported that RNA Binding Motif Protein 24 (RBM24) plays pivotal roles in stereocilia development and maintenance by regulating pre-mRNA alternative splicing and mRNA stability. In the present work, we show that exon 4 of the mouse Rbm24 gene is subjected to alternative splicing. Inclusion of exon 4 in Rbm24 mRNA results in premature translational stop, giving rise to a short isoform of RBM24 (RBM24-S). Notably, while sharing the same RNA-recognition motif, the canonical RBM24 long isoform (RBM24-L) and RBM24-S can bind different mRNA targets to affect their splicing and/or stability. Deletion of Rbm24 exon 4 in mice abolishes the expression of Rbm24(+e4) transcripts that encode for RBM24-S, and both homozygote and heterozygote mice suffer from severe hearing loss. Further investigations revealed that Rbm24 exon 4 deletion leads to stereocilia disorganization and eventually hair cell loss. Moreover, overexpression of RBM24-L in the hair cells leads to significant stereocilia deficits as well as profound hearing loss. Finally, we identified several RBM24 targets such as Strc , whose dysregulation contributes to stereocilia disorganization as well as hearing loss in Rbm24 deficient mice. Taken together, our present data suggest that Rbm24 is subjected to alternative splicing and appropriate RBM24 expression levels are important for stereocilia integrity and hearing function.